Development of Gas Leakage Monitoring Based on Smartphone Application - Muhammad Qhayyiem Isa; Ab Ghafar, Aimi Syamimi (Progress in Engineering Application and Technology, 2024)
This project focuses on developing a gas leakage monitoring system with a smartphone app created using MIT App Inventor. The system integrates an MQ2 Gas Sensor, Piezo Buzzer, and NodeMCU ESP32, connected through Blynk and Node-RED. It offers real-time gas level monitoring and triggers alerts via the Piezo Buzzer in case of an issue. Data, including sensor readings, is sent to the Blynk app for online monitoring. This project addresses the need for an affordable and efficient gas leakage monitoring system, specifically designed to integrate with smartphones, ensuring safety across different environments. The success of the system lies in enabling users to actively monitor gas leakage through the application.